ANALISIS PENGENDALIAN FOOD COST PADA HOTEL THE ST. REGIS BALI RESORT - I GUSTI MADE DENDY PRANATHA MAHARDIKA; I PUTU YOGA LAKSANA; MADE AYU JAYANTI PRITA UTAMI (Universitas Mahasaraswati K. Mataram, 2024)
This research examines food cost control at The St. Regis Bali Resort uses the Committee of Sponsoring Organizations (COSO) framework which includes five main components of internal control. The study revealed that although the resort implemented a comprehensive control system, there were some gaps between implementation and ideal food cost control practices. The main findings show the existence of food cost variances caused by ineffective and inefficient controls. Several important factors that contribute to this problem include: delays in sending market lists and purchase requisitions from the kitchen to the purchasing department, receiving invoices that do not match the purchase order, and receiving scribbled notes from suppliers. This research also identified non-compliance with standard procedures in the process of purchasing and receiving food ingredients. For example, the purchasing department sometimes makes purchases outside the specified suppliers, while the goods receiving department faces price inconsistencies from suppliers. These gaps hinder the achievement of optimal food cost control targets and have the potential to affect the company's financial stability. This study emphasizes the importance of implementing a tighter and more consistent internal control system to increase the effectiveness and efficiency of food cost control at The St. Regis Bali Resort